EVALUATION OF IN VIVO ANTI-DIABETIC ACTIVITY OF ROOT OF CRATAEVA MAGNA LOUR., ON STREPTOZOTOCIN-INDUCED DIABETIC RATS - M, SAKTHI ABIRAMI; A, MANOJKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The purpose of the study is to evaluate the anti-diabetic effect of the ethanolic extract of root of Crataeva magna Lour., on streptozotocin-induced diabetic rats. Methods: Streptozotocin (45 mg/kg) was used to induce the diabetes mellitus in rats. Afterward, the diabetic rats will be divided into four groups Group I rats served as diabetic control rats, Group II rats were induced diabetes and treated with standard drug through oral intragastric tube, Group III and Group IV were treated with ethanolic extract (200 and 400 mg/kg). Glibenclamide as reference was to evaluate the effect of the extract. Results: The administration of extract decreased the fasting blood glucose and body weight as well as increased level of total cholesterol and triglycerides which and decreased and HDL level. SGPT and SGOT level were significantly reduced in treatment group. Blood urea and creatinine were a significant difference in blood urea and creatinine. Conclusion: The extract of C.magna Lour. exhibited significant anti-diabetic activity evident from blood glucose level, body weight, serum cholesterol profile, SGOT, SGPT, serum creatinine, and serum urea level.